PRIORITIES IN UNIVERSITY TRAINING THAT PROMOTE JOB RETENTION, PERSPECTIVE OF THE HEALTH PROFESSIONAL, AYACUCHO - Miranda Ramón, Eva Iliana (2021)
Objective: To analyze the priorities in university training that promote job retention in the first level of care, from the perspective of the health professional who works in rural areas of Ayacucho. Materials and methods: The study was of a qualitative descriptive approach. Semi-structured interviews were conducted with 90 professionals who work in health facilities of three health networks located in extremely poor districts. The statements were analyzed through thematic analysis and the theoretical framework of the World Health Organization was used. Results: Four categories emerged: The university training of health professionals should be based 1) on health priorities, 2) work with the community and community prevention, 3) management of health services and (4) training interprofessional, social skills and career advancement. Conclusions: Universities that train health professionals must implement these recommendations to favor the attraction and retention of personnel in rural areas and who provide health care to extremely poor populations.